Merry Christmas - Sirett, Dawn; Bates, Eleanor (London DK Publishing, 2018)
Just right for sharing with babies and toddlers, inside you meet jolly characters and Christmassy things, all with touch and feel patches or sparkly areas to explore. There's a toy snowman with a fleecy scarf, a toy robin with a fluffy red breast, a sparkly Christmas tree, a toy reindeer with bumpy antlers, a toy elf with glittery clothes, a silky Christmas sack filled with presents, and Santa with a soft white
Picture books
1 2 23
Keywords: Board books; Christmas stories